The Parhalaan of the Batak Ugamo Malim in the arithmetic context - Ruth Mayasari Simanjuntak; Agusmanto JB Hutauruk; Efron Manik (State Islamic University of North Sumatra, 2024)
The implementation of ethnomathematics approaches that connect culture and mathematics education remains limited, despite the need to bridge mathematical concepts with real-world applications rooted in local culture. The Batak Parhalaan calendar, which incorporates arithmetic computations, has not been extensively explored within mathematics education. Prior studies often focus broadly on ethnomathematics without delving into specific cultural contexts, such as traditional calendars and their relevance to learning mathematics. This study addresses this gap by investigating how the Parhalaan calendar can be integrated into mathematics instruction to enhance students' understanding of mathematical concepts. Employing a qualitative descriptive approach, this research examines the Batak Ugamo Malim tribe's calendar system, calculates Parhalaan in relation to arithmetic, and analyzes it from a mathematical perspective. The results reveal the application of modulo arithmetic in Parhalaan, specifically the modulo 7 system, which reflects the 7-day week structure. Results reveal the application of modulo arithmetic in Parhalaan, specifically the modulo 7 system, reflecting the 7-day week structure. The formula X+Y−Z=S mod 7 harmonizes the traditional Batak calendar with the Gregorian system, providing a systematic method for determining days. Integrating this concept into mathematics education strengthens problem-solving, logical reasoning, and interdisciplinary understanding. Linking mathematics with cultural traditions fosters appreciation for local heritage, broadens perspectives, and raises awareness about preserving cultural diversity, thereby enriching the educational experience for students.